K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

\(\left(2^x+5\right)^2=169\)

=>\(\left[{}\begin{matrix}2^x+5=13\\2^x+5=-13\end{matrix}\right.\)

=>\(\left[{}\begin{matrix}2^x=13-5=8\left(nhận\right)\\2^x=-13-5=-18\left(loại\right)\end{matrix}\right.\)

=>\(2^x=8\)

=>x=3

6 tháng 11 2024

( 2x + 5 )2 = 169

(2x + 5 )2 = 132

 2x + 5 = 13 

2x = 13 - 5

2x = 8 

2x = 23

x = 3 

Vậy  x = 3

19 tháng 5 2016

A) \(\frac{7^{2003}+7^{2002}}{7^{2004}}=\frac{7^{2003}}{7^{2004}}+\frac{7^{2002}}{7^{2004}}=\frac{1}{7}+\frac{1}{7^2}=\frac{8}{49}\)

B) Xem lại đề bài

5 tháng 7 2019

( 169 - 42 ).( 169 - 52 ).( 169 - 62 )........( 169 - 142 ).( 169 - 152 )

= ( 132 - 42 ).( 132 - 52 ).( 132 - 62 )........( 132 - 132 ).( 132 - 142 ).( 132 - 152 )

= ( 132 - 42 ).( 132 - 52 ).( 132 - 62 ) ........0.( 132 - 142 ).( 132 - 152 )

= 0

24 tháng 10 2015

 

(169-42).(169-52)…(169-122).(169-132)

=(169-42).(169-52)…(169-122).(169-169)

=(169-42).(169-52)…(169-122).0

=0

(169 - 4^2) . (169 - 5^2) ... (169 - 13^2)

=(169-4^2).(169-5^2)...(169-169)

=0

16 tháng 7 2015

(169 - 4 mũ 2) (169 -5 mũ 2) ...( 169 - 13 mũ 2)

= (169-42)(169-52)...(169-132)

=(199-42)(169-52)...(169-169)

=_____________...0

=       0

18 tháng 7 2018

=(169-4^2).(169-5^20).....(169-169)

= 169-4^2).(169-5^20).......0

= 0

18 tháng 7 2018

\(=0\)

13 tháng 7 2019

a) (54 + 57) . (89 - 27) . (24 - 42

= (54 + 57) . (89 - 27) . (16 - 16)  

= (54 + 57) . (89 - 27) . 0

= 0

b) (72003 + 72002) : 72001

= 72003 : 72001 + 72002 : 72001

= 72 + 7

= 49 + 7

= 53

c) (169 - 42 ) × ( 169 - 5) ×......× ( 169 - 132)

= (169 - 42 ) × ( 169 - 5) ×......× ( 169 - 169)

= (169 - 42 ) × ( 169 - 5) ×......× 0

= 0

Tìm x biết

 7 × ( x - 14 ) + 39 = 25 + 279 ÷ 9

=> 7 × ( x - 14 ) + 39 = 25 + 31

=> 7 × ( x - 14 ) + 39 = 56

=> 7 × (x - 14)            = 56 - 39

=> 7 × (x - 14)            = 17

=>         x - 14            = 17 : 7

=>         x - 14            = 17/7

=>         x                   = 17/7 + 14

=>         x                   = 115/7 

13 tháng 7 2019

\((5^4+4^7)\times(8^9-2^7)\times(2^4-4^2)\)

\(=(5^4+4^7)\times(8^9-2^7)\times0\)

\(=0\)